(untitled) (Journal of Bangladesh Academy of Sciences, 2026)
Dopamine (DA) is a key neurotransmitter in both the brain and the body, playing a significant role in a wide range of physiological functions. However, the presence of abnormal DA levels in the body is correlated with various health conditions. Thus, for the quantification and monitoring of DA, inventing a specific and sensitive detection method is a pressing need. In the present study, an Ag/Meso-C/Polyaniline (PAni) nanocomposite is deposited over the glassy carbon electrode (GCE) to design a highly efficient DA electrochemcial sensor. The electrocatalyst was synthesized via a facile ultrasonication and followed by photo-reduction. Then, sophisticated analytical techniques were applied to investigate its structural and morphological properties. Finally, the electrochemical performance of the Ag/Meso-C/PAni nanocomposite modified electrode was evaluated by using well-known electrochemical techniques. Obtained results demonstrated high sensitivity, which was estimated to be 0.228 μA μM-1 cm-2 (for differential pulse voltammetry, DPV) and 0.166 μA μM-1 cm-2 (for amperometry). This sensor also exhibits strong selective capability in the presence of common organic and inorganic species. Finally, the successful recovery analysis was conducted in the presence of a pharmaceutical formulation and blood serum. J. Bangladesh Acad. Sci. 50(2); 215–232: June 2026